Procedural modeling historical buildings for serious games - Gonzalo Besuievsky; Gustavo Patow (Virtual Archaeology Review)
In this paper we target the goal of obtaining detailed historical virtual buildings, like a castle or a city old town, through a methodology that facilitates their reconstruction. We allow having in a short time an approximation model that is flexible for being explored, analyzed and eventually modified. This is crucial for serious game development pipelines, whose objective is focused not only on accuracy and realism, but also on transmitting a sense of immersion to the player.